Type of structure of men body engaged in baseball - Jagiello Wladyslaw.; Jagiello Marina.; Kozina Zh.L. (Fizičeskoe Vospitanie Studentov, 2012)
An attempt to define the features of structure of sportsmen body - members of collapsible command of Poland on baseball is in-process undertaken (n=20). Age of sportsmen was in a range 18-25 years, and training experience - 7-14 years. Five coefficients (Rohrera, Queteleta II, Manouvrier, growing-gravimetric, pelvic-humeral), and also general surface of body, are certain. Specific gravity of body is expected on the basis of measurings dermic-fatty folds by the use of prognostic equalization of Piechaczka. General fat in a percentage ratio to mass of body is expected on the formula of Brozka i Keys. 20 indexes are in general complication certain. On the basis of their setting of norms the type of structure of body of examinee is set. A comparative group was made by the students of the Warsaw polytechnic institute. The members of masculine collapsible command of Poland differ on baseball, foremost, by the high indexes of diameter of forearm, widths of elbow, surface and mass of body, diameter of shin.